FORMATIVE NEEDS: CONTINUING EDUCATION IN FIELD SCHOOLS - Silva Degrande, Deize Heloiza [UNESP]; Gomes, Alberto Albuquerque [UNESP] (Univ Federal Mato Grosso Sul, 2021)
This article is the extension of a Master's Dissertation that addresses reflections on the continuing education needs of teachers working in public schools in the countryside. When researching this topic, the following questions arose: How has the process of continuing education of teachers in public schools in the countryside taken place? What are your continuing education needs? The theoretical framework corresponded to studies on training needs, continuing education and field education. As a general objective we seek to analyze how the teachers of the field school understand their training needs. This research had a qualitative approach, therefore, we opted for bibliographic review and semi-structured interview, in order to investigate what are the training needs of teachers in the field. The subjects participating in our research were five teachers working in elementary and high school at the State School Luiza Maria da Cruz of the state network of Andradina/SP. The data collection guided us to results that show two main professional needs, in addition to the need to prepare teachers with theoretical and practical knowledge to work in rural schools.
Keywords: Ongoing teacher training; Countryside school; Formative needs